2020
DOI: 10.1166/jnn.2020.18487
|View full text |Cite
|
Sign up to set email alerts
|

Modification Effects of Nano-CaCO3 on Engineering Performance of Cement Grouts

Abstract: Efficacy of added nano-CaCO3 (NC) on engineering performances, including fluidity, initial setting time, bleeding rate and yield stress of cement grouts was investigated in this study. Results showed that the fluidity and bleeding rate for NC-cement (NCC) composite grout first decreased with increased NC content (i.e., ratio of NC mass to cement mass) and then slightly recovered as the NC content exceeded 2%. The initial setting time was always reduced while the yield stress increased with increased NC conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…At present, the appropriate amount of nanoadditives in the existing materials can effectively improve the relevant physical and mechanical parameters of the materials, formulate mixed materials suitable for different needs, and increase the scope of the original materials [9][10][11][12][13][14]. In terms of improving the cement substrate, Wang et al found that adding nano-CaCO 3 into Portland cement can significantly improve the mechanical properties of cement-based materials and make the cement substrate more uniform.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the appropriate amount of nanoadditives in the existing materials can effectively improve the relevant physical and mechanical parameters of the materials, formulate mixed materials suitable for different needs, and increase the scope of the original materials [9][10][11][12][13][14]. In terms of improving the cement substrate, Wang et al found that adding nano-CaCO 3 into Portland cement can significantly improve the mechanical properties of cement-based materials and make the cement substrate more uniform.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies [ 15 , 18 ], nano-SiO 2 can also play a significant role in early strength at the curing age of 7 days for common cement-based materials. In contrast, the effect of nano-SiO 2 weakened at the curing age of 3 days and disappeared at the curing age of 7 days for the HCGA proposed in this study.…”
Section: Hydration Mechanisms Of Hcgamentioning
confidence: 99%
“…Feng et al [ 17 ] proved the significance of nano-SiO 2 on the early age hydration of cement mortars. Qiu et al [ 18 ] revealed the modification effects of nano-CaCO 3 on the engineering performance of cement grouts. Jiao et al [ 19 ] proved the feasibility of nano-Fe 3 O 4 used in cement paste.…”
Section: Introductionmentioning
confidence: 99%